2023
DOI: 10.1098/rspb.2022.2263
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and nutrients drive eco-phenotypic dynamics in a microbial food web

Abstract: Anthropogenic increases in temperature and nutrient loads will likely impact food web structure and stability. Although their independent effects have been reasonably well studied, their joint effects—particularly on coupled ecological and phenotypic dynamics—remain poorly understood. Here we experimentally manipulated temperature and nutrient levels in microbial food webs and used time-series analysis to quantify the strength of reciprocal effects between ecological and phenotypic dynamics across trophic leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…S10). We find strong support for a super-linear scaling relationship between body size and volume that indicates protist populations might undergo density-dependent (population) and density-independent (individual phenotypic) responses to climate change (41, 61, 87, 98, 99). Our results indicate a significant relationship between proportional change of traits and size—larger protists’ size (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…S10). We find strong support for a super-linear scaling relationship between body size and volume that indicates protist populations might undergo density-dependent (population) and density-independent (individual phenotypic) responses to climate change (41, 61, 87, 98, 99). Our results indicate a significant relationship between proportional change of traits and size—larger protists’ size (Fig.…”
Section: Discussionmentioning
confidence: 64%
“…We found that overall, the trend reversals reported here (biomass, abundance, traits) were size-dependent (Figure S14). We find strong support for a super-linear scaling relationship between body size and volume that indicates protist populations might undergo density-dependent (population) and density-independent (individual phenotypic) responses to climate change (Gibert et al, 2022(Gibert et al, , 2023Han et al, 2023;Wieczynski et al, 2021;Yoshida et al, 2003).…”
Section: Red To Green Ratio (D)mentioning
confidence: 63%
“…There is growing recognition that temperature and nutrients interact to impact the structure and dynamics of ecological communities (Binzer et al, 2012(Binzer et al, , 2016Gilbert et al, 2014;Han et al, 2023;Sentis et al, 2014). Discovering conditions under which temperature-nutrient interactions occur and which properties of ecological systems are affected (e.g.…”
Section: Discussionmentioning
confidence: 99%